Pengaruh Penerapan Model Pembelajaran Problem Based Learning (PBL) terhadap Hasil Belajar Siswa pada Mata Pelajaran IPAS di Kelas IV Sekolah Dasar Negeri 03 Pontianak Selatan - Nur Azizah; Hery Kresnadi; Rio Pranata (Journal on Education, 2024)
This study aimed to describe the influence of the application of Problem Based Learning model (PBL) on students' learning outcomes in IPAS subjects in class IV of Negeri Elementary School 03 Pontianak Selatan. The method used is an experiment in the form of Quasi-Experimental Design with a type of one group pre test-post test design. The population is the entire class of IV students consisting of 4 classes. This study sample was class IV A students totaling 28 students and class IV B students totaling 28 students. The data collection technique used is a measurement technique and the data collection tool is a multiple choice shaped written test. Based on the data analysis, the average results of the final tests of the experimental class and the average of the final tests of the control class were obtained. Hypothetical test results using t-test (separates variance) were obtained thitung = 11.9647, while for dk (28 + 28 - 2 = 54) with a significant degree α = 5%, ttable = 2.0518 meaning thitung > ttable, then Ha is accepted, this proves that there is an influence of Problem Based Learning model (PBL) on the outcome of secondary learning in IPAS subjects. Based on the results of the calculation of effect size (ES), ES = 0.62 is obtained, which includes the moderate criterion. Thus, it can be concluded that the problem-based learning model has a positive influence on students' learning outcomes in IPAS subjects in class IV SD Negeri 03 Pontianak Selatan.